Gerald R. McDermott, Ed. Understanding the Jewish Roots of Christianity: Biblical, Theological, and Historical Essays on the Relationship between Christianity and Judaism - Zaas, Peter (Studies in Christian-Jewish Relations, 2022)
No abstract is available.